2018
DOI: 10.1186/s12871-018-0486-8
|View full text |Cite
|
Sign up to set email alerts
|

Unusual elevation in Entropy but not in PSI during general anesthesia: a case report

Abstract: BackgroundEEG monitoring is useful for determining an adequate level of anesthesia. However it is sometimes interfered by various reasons. We describe a case in which we successfully confirmed the adequate depth of anesthesia by monitoring the patient state index (PSI), which was computed from the SedLine monitor data in Root (Masimo) during general anesthesia. Our case showed unusual elevations in entropy, but not in PSI.Case presentationA 34-year-old woman was scheduled for emergency surgery for a left tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Another experienced implication was studied by Aho et al, they found inconsistent values recorded by entropy concomitantly with raw EEG signal during general anaesthesia, electrocautery-induced artefacts. episodic EMG activity revealed non-relevant BIS and entropy indices with the raw EEG signals [12].…”
Section: Discussionmentioning
confidence: 99%
“…Another experienced implication was studied by Aho et al, they found inconsistent values recorded by entropy concomitantly with raw EEG signal during general anaesthesia, electrocautery-induced artefacts. episodic EMG activity revealed non-relevant BIS and entropy indices with the raw EEG signals [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al. 10 added support to this contention with a case of an unusual increase in entropy by EMG activity, which was not indicated by the patient state index.…”
Section: Discussionmentioning
confidence: 98%
“…Despite these limitations, our results provide meaningful information in interpreting the BIS and entropy in children with cerebral palsy, in whom entropy may help distinguish consciousness from unconsciousness as well as the BIS. Considering that entropy describes the irregularity, complexity, or unpredictability of the EEG [ 20 ] and assuming that BIS reflects the EEG characteristics of the general population (see the Appendix ), entropy may be useful for CP patients. Furthermore, looking to exhibiting hysteresis, both BIS and entropy can be said to suggest that the limits of the EEG signal processing for real-time evaluation of consciousness [ 21 ].…”
Section: Discussionmentioning
confidence: 99%